TABOT Upacara Tradisi Masyarakat Pesisir Bengkulu - Renta, Person Pesona (Fakultas Ilmu Budaya Universitas Diponegoro, 2011)
The traditional ceremony of Tabot in Bengkulu is basically to commemorate the suicide of Hassan and Hussein, the grandson of the Prophet Muhammad as martyrs in the field of Karbala. Ceremony of Tabot in Bengkulu was brought by Muslims from India who were working to build the Port of Marlborough in the 17th century AD. Tabot laden with religious rituals, ranging from the preparation, implementation until the end of the ceremony. Tabot is also laden with religious symbols that contain the meaning within. Although not an original culture, Tabot in Bengkulu has become a tradition that does not conflict with the local culture, so that it can be accepted by the community. Ceremony of Tabot in Bengkulu is a tradition held annually by the family descendants of the Tabot from date 1 to date 10 Muharram in Hijri and ends with